2015
DOI: 10.1186/s12882-015-0130-5
|View full text |Cite
|
Sign up to set email alerts
|

Orally active prostacyclin analogue beraprost sodium in patients with chronic kidney disease: a randomized, double-blind, placebo-controlled, phase II dose finding trial

Abstract: BackgroundEvidence increasingly points to the importance of chronic hypoxia in the tubulointerstitium as a final common pathway to end-stage renal disease (ESRD). Beraprost sodium (BPS) is an orally active prostacyclin (PGI2) analogue demonstrating prevention of the progression of chronic kidney disease (CKD) in various animal models by maintaining renal blood flow and attenuating renal ischemic condition.MethodsThis multicenter, randomized, double-blind, placebo-controlled, phase II trial was designed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
5
19
0
Order By: Relevance
“…On the other hand, regarding safety, no relationship was observed between the incidence of adverse events and the severity of impaired kidney function following the single oral administration of 120 μg of BPS, and the tolerability was confirmed in subjects with impaired kidney function. Because the tolerability was also confirmed in patients with impaired kidney function in a phase 2 trial (120 μg BID for 26 weeks), the safety in subjects with impaired kidney function in the present study was no problem. Furthermore, in the phase 2 trial, a significant improvement in the ratio of SCr was achieved in the 120‐μg group (60 μg BID) as well as in the 240‐μg group (120 μg BID), independent of blood pressure or urinary protein levels .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…On the other hand, regarding safety, no relationship was observed between the incidence of adverse events and the severity of impaired kidney function following the single oral administration of 120 μg of BPS, and the tolerability was confirmed in subjects with impaired kidney function. Because the tolerability was also confirmed in patients with impaired kidney function in a phase 2 trial (120 μg BID for 26 weeks), the safety in subjects with impaired kidney function in the present study was no problem. Furthermore, in the phase 2 trial, a significant improvement in the ratio of SCr was achieved in the 120‐μg group (60 μg BID) as well as in the 240‐μg group (120 μg BID), independent of blood pressure or urinary protein levels .…”
Section: Discussionsupporting
confidence: 54%
“…Because the tolerability was also confirmed in patients with impaired kidney function in a phase 2 trial (120 μg BID for 26 weeks), the safety in subjects with impaired kidney function in the present study was no problem. Furthermore, in the phase 2 trial, a significant improvement in the ratio of SCr was achieved in the 120‐μg group (60 μg BID) as well as in the 240‐μg group (120 μg BID), independent of blood pressure or urinary protein levels . Therefore, we consider that the pharmacokinetics changes of BPS and BPS‐314 d accompanied with impaired kidney function are not clinically relevant, and the dose adjustment is not necessary in patients with impaired kidney function.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, we estimated the 55 μg/body dose in this study would not have acute action to reduce the blood pressure; in a study using healthy cats, we had confirmed BPS at doses up to 100 μg/kg had no influence on the blood pressure . Furthermore, a human study also suggests that BPS inhibits increase in the sCr without lowering the blood pressure . Thus, it is unlikely that reduced blood pressure might be involved in the mechanism of action of BPS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from CRF could be more susceptible to other conditions, such as coronary artery diseases, ultimately leading to a decrease in quality of life and even death [15]. Recently, Koyama et al revealed that BPS served as a therapeutic treatment for chronic kidney disease (CKD) in several animal models [16]. Hence, based on this evidence, we hypothesized that BPS, as a stable analogue of PGI2, could influence the local RAS in rats with CRF.…”
Section: Discussionmentioning
confidence: 99%